A global redistributive auction for vaccine allocation - Sterri, AB; Skjelbred, P (BMJ Publishing Group, 2024)
The global allocation of vaccines during the COVID-19 pandemic is widely perceived as unfair. Priority was given to countries that paid the most with little or no concern for who needed the vaccines the most. No satisfactory institutions have been established to allocate vaccines in a future pandemic. In this paper, we join reformers in proposing a new scheme for vaccine distribution: a global auction for vaccines where profits are distributed fairly to participating countries. Our proposal improves upon previous suggestions morally by taking countries' differing valuations of money and vaccines seriously. Since an auction is in the interest of both vaccine manufacturers and high-income countries, it is also politically feasible. A global redistributive auction for vaccines thus promises to be a robust and morally desirable way to allocate vaccines.